The method of the Jurisprudence Extracted from the Qur’an for Al-Imam Ash-Shafi^iyy and his affiliated jurists - A comparative study - A Sample of The Verses Pertaining to the Judgments of Purification – - Khoudari, Soubhiya Hamed (Journal of Islamic Sciences, 2022)
The fundamental goal of this study is to discuss an aspect of the comparison between the methodologies of Islamic jurisprudence. That is the aspect of extracting judgments from the Qur’an; i.e., how the judgments were extracted from the verses of the Qur’an. I bring to light the disagreements between the judicial school of Al-Imam Ash-Shafi^iyy with his affiliated jurists and other judicial schools pertaining to some of the evidence for the rules of ritual purification. During an in-depth, encompassing, comparative examination, I clarified the different methodologies the scholars used in addressing with the same evidence, the reasons for their differences, and the results of those differences, like the enumeration of opinions about the judgment of a single case, and the branching out of the regarded opinions about that case, to the extent that it is permissible for the non-jurist, i.e., the follower to take by and implement any one of these opinions. This contains ease and relief from Allah, the Exalted, for His slaves.